Мовні засоби вираження простору в поезії Лесі Українки - Іовхімчук, Наталія Володимирівна; Iovkhimchuk, Nataliia V. (My University, 2015)
У роботі зроблено спробу виокремити номінації простору та мовні засоби їх вираження у мові поезії Лесі Українки. Досліджуються особливості художнього простору, який умовно поділено на горизонтальний (нижній) і вертикальний (верхній) світи. In this work we tvied to separate the nominations of space and language methodof, its expression in the poetic language of Lesia Ukrainka. The particular features of artistic space are explored this space is imaginary divided into horisontal (low) and vertical (high) worlds.
Language means of expression space in poetry of Lesya Ukrainian
Keywords: номінації простору; горизонтальний простір; вертикальний простір; nominations of space horisontal; vertical space